Copyrighting god: ownership of the sacred in American religion - Ventimiglia, Andrew (Cambridge University Press, 2019)
Copyrighting God provides the first detailed account of how American religious organizations used copyright in sacred texts not simply for economic gain but also for social organization and control. Including chapters on the angelic authorship of The Urantia Book, Mary Baker Eddy's use of copyright to construct the Christian Science Church, interdenominational disputes in the Worldwide Church of God, and the Church of Scientology's landmark lawsuits against Internet service providers, this book examines how religious copyright owners mobilized the law in order to organize communities, protect sacred goods, produce new forms of spiritual identity, and even enchant the material world. In doing so, this book demonstrates that these organizations all engaged in complex efforts to harmonize legal arguments and theological rationales in order to care for and protect religious media, thereby coming to a nuanced understanding of secular law as a resource for, and obstacle to, their unique spiritual objectives.